Проєктування підсилювача потужності для підсилювач сигналу стільникового звязку - Варейчук, В. Е. (ХНУРЕ, 2024)
This work is devoted to the topic of cellular signal amplifiers. They serve to strengthen the signal and local expansion of the network coverage area. A low-noise power amplifier for receiving the reception path of GSM standards at frequencies of 890 - 915 MHz has been designed.
Keywords: підсилювач потужності; підсилювач сигналу стільникового звязку